2017
DOI: 10.1016/j.biopsych.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor Receptor 1 Antagonism Is Ineffective for Women With Posttraumatic Stress Disorder

Abstract: Background Medication and psychotherapy treatments for posttraumatic stress disorder (PTSD) provide insufficient benefit for many patients. Substantial preclinical and clinical data indicate abnormalities in the hypothalamic-pituitary-adrenal axis, including signaling by corticotropin-releasing factor, in the pathophysiology of PTSD. Methods We conducted a double-blind, placebo-controlled, randomized, fixed-dose clinical trial evaluating the efficacy of GSK561679, a corticotropin-releasing factor receptor ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 78 publications
(67 reference statements)
1
76
2
Order By: Relevance
“…A limitation of the current study is that only women were included (Dunlop et al, ). Additionally, the conditional discrimination paradigm is sensitive to cycle effects and estradiol level (Glover et al, ), which were not controlled in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A limitation of the current study is that only women were included (Dunlop et al, ). Additionally, the conditional discrimination paradigm is sensitive to cycle effects and estradiol level (Glover et al, ), which were not controlled in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we have found that this specific deficit, rather than a more broad learning deficit, is associated with higher PTSD symptoms (Jovanovic et al, ). The larger clinical trial of GSK561679 did not find therapeutic benefits of the drug in reducing PTSD symptoms (Dunlop et al, ). One of the possible interpretations of the negative results is that the effects of CRF receptor 1 antagonism may vary based on the degree of receptor binding in different brain regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the first molecules tested, R121919, showed some promise in depression, but development of the drug was suspended due to elevations in liver enzymes (Zobel et al 2000). Other small molecule CRFR1 antagonists have been tested in depression, anxiety, human fear lab studies, and PTSD but all have yielded negative results (Binneman et al 2008; Coric et al 2010; Dunlop et al 2017; Grillon et al 2015). Two studies have examined the efficacy of CRFR1 antagonists for decreasing craving in anxious adults with AUD.…”
Section: Human Studiesmentioning
confidence: 99%